Cost of preterm birth to Australian mothers: Assessing the financial impact of a birth outcome with an increasing prevalence. (10th January 2021) - Fox, Haylee; Callander, Emily
Abstract : Aim: To examine the differences in return to work time after childbirth; the differences in income; and the differences in out of pocket health‐care costs between mothers who had a preterm birth and mothers who delivered a full term baby in Australia. Methods: Using administrative data, the length of time and 'risk' of returning to employment for mothers whose child was born premature relative to those whose child was born full term was reported. Multivariate linear regression models were constructed to assess the difference in maternal income and the differences in mean out‐of‐pocket costs between mothers who had a preterm birth and mothers who had a full term birth. Results: The mean length of time for mothers of babies born full term to return to work was 1.9 years and for mothers of preterm babies it was 2.8 years. Mothers of preterm babies had a significantly lower median income ah at 0–1, 2–3 and 4–5 years postpartum compared to mothers of full term babies. The adjusted mean out of pocket costs for health care paid by mothers who had a preterm birth was $1298 for those whose child was aged 32–36 weeks; and $2491 for those whose child was aged <32 weeks. This is in comparison to mothers of children born 37 weeks and over, whose mean out of pocket costs were $1059. Conclusion: Mothers who have a preterm birth have longer return to work time, a lower weekly income and also have higher out of pocket costs compared with mothers who have a full term birth.